2020
DOI: 10.1093/toxsci/kfaa132
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Effects of Exposure to Aerosol From the Candidate Modified-Risk Tobacco Product THS 2.2 in an 18-Month Systems Toxicology Study With A/J Mice

Abstract: Smoking cessation is the most effective measure for reducing the risk of smoking-related diseases. However, switching to less harmful products (modified risk tobacco products [MRTP]) can be an alternative to help reduce the risk for adult smokers who would otherwise continue to smoke. In an 18-month chronic carcinogenicity/toxicity study in A/J mice (OECD Test Guideline 453), we assessed the aerosol of Tobacco Heating System 2.2 (THS 2.2), a candidate MRTP based on the heat-not-burn principle, compared with 3R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…This publication describes the study design, analytical characterization of selected aerosol constituents in the test atmospheres, biomarkers of exposure in the blood and urine samples of exposed mice, general health conditions of the mice, and histopathological findings of nonrespiratory and respiratory tract organs, including those of nonproliferative and proliferative respiratory tract lesions. The results of extensive omics analyses of nasal and laryngeal epithelia and the lungs collected from mice in this study are reported separately ( Titz et al , 2020 ).…”
mentioning
confidence: 99%
“…This publication describes the study design, analytical characterization of selected aerosol constituents in the test atmospheres, biomarkers of exposure in the blood and urine samples of exposed mice, general health conditions of the mice, and histopathological findings of nonrespiratory and respiratory tract organs, including those of nonproliferative and proliferative respiratory tract lesions. The results of extensive omics analyses of nasal and laryngeal epithelia and the lungs collected from mice in this study are reported separately ( Titz et al , 2020 ).…”
mentioning
confidence: 99%
“…Clear effects were observed upon smoke exposure to cigarette smoke. No increased incidence and multiplicity in pre-neoplastic and neoplastic changes were observed in the lungs of HTP aerosol-exposed mice, even at twice the concentration of nicotine in the aerosol (15,16).…”
Section: Does Switching Completely To Htp Reduce the Negative Health Effects Compared To Continuing Smoking?mentioning
confidence: 86%
“…With respect to the findings of these studies, classical histopathological analyses have indicated that exposure to aerosol from heated tobacco products consistently yielded significantly reduced biological effects when compared to those observed with conventional cigarettes in a range of tissues including the respiratory tract (Phillips et al, 2016(Phillips et al, , 2019Titz et al, 2016Titz et al, , 2020aOviedo et al, 2016;Wong et al, 2016), cardiovascular system (Phillips et al, 2016;Szostak et al, 2020), liver (Lo Sasso et al, 2016aWong et al, 2016) and gastrointestinal tract (Battey et al, 2021). Observations from a life-time exposure study using A/J mice with an 18-month exposure period indicated that chronic exposure to aerosol from the THS 2.2 heated tobacco product did not increase the incidence or multiplicity of bronchioalveolar adenomas or carcinomas relative to sham-exposed mice whilst exposure to mainstream smoke from the 3R4F Kentucky reference cigarette did (Wong et al, 2020).…”
Section: Chronic Rodent Exposure Studiesmentioning
confidence: 98%
“…Exposure to aerosols has been on comparable nicotine concentrations (expressed either as mg/m 3 or μg/L) with several concentrations used for either or both of the aerosols. Exposure periods have ranged from thirty-five and/or ninety days (Terpstra et al, 2003;Moennikes et al, 2008;Werley et al, 2008;Oviedo et al, 2016;Wong et al, 2016) to six months or more [not including any additional recovery periods] (Phillips et al, 2016(Phillips et al, , 2019Lo Sasso et al, 2016a;Titz et al, 2016Titz et al, , 2020aSzostak et al, 2017;Choukrallah et al, 2019;Szostak et al, 2020;Wong et al, 2020;Battey et al, 2021). The suitability of the Apo E -/mouse as an experimental model for studying the effects of both conventional cigarette smoke and heated tobacco product aerosol exposures on cardiovascular and respiratory disease end-points has been discussed elsewhere by separate authors (Lo Sasso et al, 2016b).…”
Section: Chronic Rodent Exposure Studiesmentioning
confidence: 99%